Organic matter concentration and composition in four trophic regimes of the South Pacific Ocean - Theresa Barthelmeß; Anja Engel (PANGAEA, 2025)
Samples were collected in the surface of the Southwestern Pacific Ocean in subtropical and sub-Antarctic water masses, above the Chatham Rise and at the entrance of the Cook Strait in well mixed water masses, creating distinct oligotrophic and eutrophic regimes, respectively. Diel dynamics in concentrations of total organic carbon and nitrogen (TOC/TON), as well as total combined carbohydrates (TCCHO) and total amino acids (TAA), and their dissolved fractions (<0.45μm) are presented. Viral particle abundance (V_III_ml) complements the flow cytometry measurements as presented in the associated dataset of Law et al.
In: Barthelmeß, Theresa; Cristi, Antonia; Deppeler, Stacy; Safi, Karl; Sellegri, Karine; Law, Cliff S; Engel, Anja (2025): Diel dissolved organic matter cycling and phytoplankton abundance in four trophic regimes of the South Pacific Ocean [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.974276